2007
DOI: 10.1108/jpbafm-19-02-2007-b006
|View full text |Cite
|
Sign up to set email alerts
|

Public pension fund governance practices and financial performance

Abstract: ABSTRACT. This study is a follow up of an earlier investigation concerning the effects of governance practices and investment strategies on public pension fund risk adjusted financial performance. Specifically, the inquiry uses three cross sectional national surveys of state and local government retirement systems to determine how governance practices in terms of system policies, board purview, and board composition impact abnormal returns. Results indicate that governance practices, particularly board purview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous studies have found mixed results on the effect of board composition on pension investment risks and asset allocations (Harper, 2008;Albrecht et al, 2007;Albrecht & Hingorani, 2004;Useem & Mitchell, 2000). Schneider and Damanpour (2001), examining this effect from the perspective of Public Choice Theory, argued that politically appointed and ex-officio board members are motivated to maximize their own interests and the interests of the state executive or legislative leaders.…”
Section: Pension Boardmentioning
confidence: 99%
“…Previous studies have found mixed results on the effect of board composition on pension investment risks and asset allocations (Harper, 2008;Albrecht et al, 2007;Albrecht & Hingorani, 2004;Useem & Mitchell, 2000). Schneider and Damanpour (2001), examining this effect from the perspective of Public Choice Theory, argued that politically appointed and ex-officio board members are motivated to maximize their own interests and the interests of the state executive or legislative leaders.…”
Section: Pension Boardmentioning
confidence: 99%
“…Prior studies have found that pension board governance could make a significant difference in the selection of investment portfolios and eventually affect the investment returns. However, empirical research provides mixed results in testing these effects (Albrecht & Hingorani, 2004;Albrecht, Shamsub, & Giannatasio, 2007;Harper, 2008;Mitchell & Hsin, 1997;Romano, 1993;Useem & Mitchell, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%